2013
DOI: 10.1155/2013/394320
|View full text |Cite
|
Sign up to set email alerts
|

Rising Prevalence and Neighborhood, Social, and Behavioral Determinants of Sleep Problems in US Children and Adolescents, 2003–2012

Abstract: We examined trends and neighborhood and sociobehavioral determinants of sleep problems in US children aged 6–17 between 2003 and 2012. The 2003, 2007, and 2011-2012 rounds of the National Survey of Children's Health were used to estimate trends and differentials in sleep problems using logistic regression. Prevalence of sleep problems increased significantly over time. The proportion of children with <7 days/week of adequate sleep increased from 31.2% in 2003 to 41.9% in 2011-2012, whereas the prevalence of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 40 publications
8
142
1
Order By: Relevance
“…Among adults, feeling unsafe is associated with adopting poorer health habits (e.g., increases in sedentary behavior, decreased physical activity, and active transportation), and experiencing poorer mental (e.g., anxiety, deteriorated psychological wellbeing, and social withdrawal) and physical (e.g., poorer self-reported health, stressrelated diseases, and chronic conditions) health. [7][8][9][10] With respect to child health, parent perceived unsafety is associated with asthma, 11 sleep problems, 12 psychological distress, 13 and weight-related behaviors (e.g., physical activity). 14 Parents' perceptions of safety may influence child health by impacting the household environment and parenting decisions (e.g., restricting children's outdoor activities).…”
mentioning
confidence: 99%
“…Among adults, feeling unsafe is associated with adopting poorer health habits (e.g., increases in sedentary behavior, decreased physical activity, and active transportation), and experiencing poorer mental (e.g., anxiety, deteriorated psychological wellbeing, and social withdrawal) and physical (e.g., poorer self-reported health, stressrelated diseases, and chronic conditions) health. [7][8][9][10] With respect to child health, parent perceived unsafety is associated with asthma, 11 sleep problems, 12 psychological distress, 13 and weight-related behaviors (e.g., physical activity). 14 Parents' perceptions of safety may influence child health by impacting the household environment and parenting decisions (e.g., restricting children's outdoor activities).…”
mentioning
confidence: 99%
“…5 Studies have found higher rates of sleep problems in children from lowincome families as well as those who live in lower-income neighbourhoods. [34][35][36] Lower SES was correlated with lower sleep duration in children. Using the Panel Survey of Income Dynamics, family income was related to shorter sleep duration.…”
Section: Discussionmentioning
confidence: 96%
“…In the United States, data from the National Survey of Children's Health show that the prevalence of sleep problems has increased significantly over the past 15 years, with 10-16% of youth currently exhibiting serious sleep problems (Singh & Kenney, 2013). Frequently occurring problems include poor sleep quality (e.g., waking up multiple times during the night), inadequate sleep duration (i.e., fewer hours slept), and daytime sleepiness (i.e., feelings of tiredness during the day).…”
Section: Prevalence Of Sleep Problems In Adolescencementioning
confidence: 99%